Prevalência das arritmas cardíacas e distúrbios de condução em cães e gatos em Botucatu, Brasil (2003-2007) - Aptekmann, Karina Preising [UNESP]; Vailati, Maria do Carmo Fernandez [UNESP]; Fortuna, Thatiana de Oliveira Moura; Schwartz, Denise Saretta (My University, 2010)
Cardiac arrhythmias are important electrocardiographic disorders in small animal medicine since some of them can cause serious situations, such as cardiac arrest and death. It's essential to recognize ECG abnormalities and the frequency they occur to improve the therapy. The aim of this study was to determine the prevalence of cardiac arrhythmias in dogs from January 2003 to April 2007 by retrospective analysis of ECGs obtained at the Veterinary Hospital at UNESP - Botucatu - SP. The most common rhythm disturbances in this population were sinus tachycardia and ventricular premature complexes in dogs and sinoventricular rhythm in cats.
Prevalence of cardiac arrhythmias and conduction disturbances in dogs and cats in Botucatu, Brazil (2003 2007)
Keywords: Arrhythmias; Cats; Dogs; Eletrocardiography; Rhythm disturbances; Animalia; Canis familiaris